Unification of free energy minimization, spatiotemporal energy, and dimension reduction models of V1 organization: Postnatal learning on an antenatal scaffold - Wright, James Joseph; Bourke, Paul David (Frontiers in Computational Neuroscience, 2022)
Developmental selection of neurons and synapses so as to maximize pulse synchrony has recently been used to explain antenatal cortical development. Consequences of the same selection process – an application of the Free Energy Principle – are here followed into the postnatal phase in V1. Input stimulus fields, transformed via lag relay in superficial patch connections, lead to generation of circumferential synaptic connectivity superimposed upon the antenatal radial “like-to-like” connectivity surrounding each singularity. Neurodynamic properties of heteroclinic networks with coupled spatial eigenmodes emerge. The spatiotemporal energy and dimension reduction models of cortical neuron feature preferences are accounted for and unified within the expanded model, and relationships of orientation preference (OP), space frequency preference (SFP) and temporal frequency preference (TFP) resolved. Prediction error minimization and learned anticipation of future inputs arise as emergent properties.